UZNADZE'S THEORY AS A CONCEPT OF PERSONALITY: https://doi.org/10.5281/zenodo.13896886 - Abdurasulov , Farkhod (Science technology&Digital finance, 2023)
The general psychological theory of D.N.Uznadze's attitude is aimed at solving fundamental methodological problems, covers the main categories of psychology: consciousness, unconscious, behavior, personality. It is relevant to all manifestations of mental activity at any level of phylogeny, ontogenesis and actualgenesis, and is aimed at studying the universal mechanism of behavior determination. At the same time, it presents a system of views on specific human activity, i.e. It includes personality theory, covering topics such as personality structure, motivation, personality development, psychopathology, mental health and personality change through psychocorrectional (psychotherapeutic) influence. The latter topic has not yet been adequately developed and represents one of the vectors of further development of this concept.